Determinan Kelengkapan Imunisasi Lanjutan pada Batita di Wilayah Kerja Puskesmas Oekabiti - Naddya Aprilia Marth Henuck; Honey Ivon Ndoen; Yuliana Radja Riwu (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Imumunization is one way to reduce infant and toddler mortality rates effectively and is the main basis for preventive health services and reducing the spread of infection. The main aim of immunization is to reduce morbidity, disability and death rates due to diseases that can be prevented by immunization (PD3I). This research aims to Determinants of Completeness of Advanced Immunizationin Children Under Three Years Old in the Work Area of Oekabiti Public Health. This type of research is analytical research using a Case Control design. The sample consist of 102 people using a simple random sampling technique. Data analysis uses univariate and bivariate analysis with the Chi-Square test with a significance level of-0,05. The research result showed that factor related to completeness of advanced immunization was education (p-value=0,001), knowledge (p-value=0,00), Post-Immunization Adverse Events (AEFI) (p-value=0,002), family support (p-value=0,001), it is hoped that mothers will pay more attention to the completeness of baby immunization and immediately take the baby to a health service if the time has come for immunization and Community Health Center needs to make efforts to increases the utilization of helath services in remote villages, such as providing counseling and outreach about the benefits of immunization for babies.